INFINITy: A fast machine learning-based application for human influenza A and B virus subtyping - Cacciabue, Marco Polo Domingo (2023)
INFINITy isa fast and accurate tool for classifying human influenza A and B virussequences into types, lineages, clades, and subclades. It is an applicationbased on an alignment-free machine learning algorithm that can classify bothcomplete hemagglutinin (HA) gene sequences or the HA1 subunit coding sequence.INFINITy was developed as a web-application and is available to run locally for R and Rstudio users.